Pengaruh Supervisi Akademik Berbasis Coaching dan Iklim Kerja Terhadap Kinerja Guru - Wulandari, Meki (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to analyze the impact of coaching-based academic supervision and work climate on the performance of junior high school teachers in Rayon 7 OKU Selatan. The research employed a quantitative method with a survey design, involving 150 teachers as the population and 100 teachers selected as a sample through random sampling. Data were collected using questionnaires that were pre-tested to ensure validity and reliability. Data analysis was conducted using descriptive statistics and multiple regression techniques to test the research hypotheses. The results indicate a significant influence of coaching-based academic supervision on teacher performance, where this approach provides more personalized support and encourages professional development among teachers. Additionally, a conducive work climate also significantly contributes to improving teacher performance, where effective communication and support from colleagues play crucial roles. The implications of these findings suggest that the development of coaching-based supervision programs and improvements in the work climate are essential for enhancing teacher performance. Educational policy recommendations focus on training for school principals and teachers in coaching techniques, as well as efforts to create a positive work environment. This study also recommends further research to explore additional factors influencing teacher performance, thereby contributing to the improvement of educational quality in Indonesia.